Review on the dual impact of social media on psychological well-being: from Nigeria context - ., Omeye; Ma’rof, Aini Azeqa (Human Resources Management Academic Research Society, 2024)
This research examines the psychological impacts of smartphone addiction, focusing specifically on its potential implications on mental well-being, in response to the growing prevalence of mobile device usage. Smartphone addiction, characterized by the excessive and dysfunctional use of cellphones, has emerged as a significant public health issue. This review aims to assess the correlation between smartphone addiction and psychiatric problems such as social isolation, anxiety, and depression by summarizing the existing literature. Empirical evidence demonstrates a definite correlation between excessive smartphone usage and a deterioration in mental well-being. Social media platforms intensify addiction by promoting the behavior of "phubbing," which involves disregarding one's surroundings in favor of using their smartphones. This behavior is responsible for the deterioration of interpersonal ties and the loss in life happiness. The paper advocates for the implementation of comprehensive strategies that integrate psychiatric therapy, public health initiatives, and technological solutions to promote digital wellness and improve technology usage patterns. To achieve effective interventions, it emphasizes the ambivalent nature of technology and promotes ongoing study and collaboration between the mental health and technology sectors. It highlights the potential of technology to both enhance and deteriorate mental health.